(untitled) (Al-Aasar, 2025)
This article critically examines the ideological confusion caused by Qurʾānists who attempt to interpret the theory of evolution in a manner that contradicts the Qurʾānic and prophetic narratives concerning the creation of ʿĀdam (Peace be Upon Him). It begins by explaining the concept of human creation based on authentic prophetic traditions, followed by a detailed evaluation of the arguments presented by those who deny ḥadīth and support evolutionary claims. The article demonstrates that, according to the Qurʾān and Sunnah, the creation of ʿĀdam was not at the species level but as an individual human being, directly refuting the idea that ʿĀdam was merely symbolic or a representation of early humanity. The research further highlights the double standards of Qurʾānists who accept unproven scientific assumptions while dismissing clear revelations. In conclusion, the article asserts that the Islamic revelation provides a complete and superior explanation for human origins—one that transcends temporary and shifting scientific theories.